Kemampuan Negosiasi Perempuan Pekerja Seks Jalanan dalam Penggunaan Kondom terhadap Pencegahan Penyakit Menular Seksual dan HIV/AIDS di Kota Jayapura - Tahi Ganyang Butarbutar, Suharyanto Supardi, Ira Paramastri (Berita Kedokteran Masyarakat (BKM), 2003)
Background: The data on HIV/AIDS in Papua by 30 August 2002 reveal 882 cases. 70 cases of HIV/AIDS are recorded in Jayapura municipality. The highest percentage of HIV/AIDS infection is for reproductive age (15-39) group, i.e., 82,9%. One of the factors affecting the intensity of HIV/AIDS infection rate in street commercial sex workers is the low level of condom use. The objectives of this research are to identify the factors that make street commercial sex workers not use condom, the social aspects that influence the negotiation, the form negotiation of condom use, and how to get a condom.Methods: The study was applied a qualitative method using a focus group discussion, in-depth interview and participatory observation. The number of subjects were 38 per-sons consisting of 20 persons from the group discussion, 13 were in-depth interviewed, and 5 were in the participatory observation type of data collection.Results: In general, despite knowing that everyone, including him or her, was vulner-able to AIDS infection, the respondents ignore asking guests or partners for condom use. Most do not ask for condom use due to their fear of either being the target of guest's anger and bad words, or losing money from them. Most of them say that they do not have written nor spoken agreement with their peers, the room and hotel owners. They do not encourage condom use, as condom is not available in the room where they do practices. Moreover, the condom package is regarded inappropriate, as it is not in accordance with the local language and cultural characteristics.Conclusion: The low capability of street commercial sex workers for negotiating con-dom use with the guest/customers results from; misperception on "safe-sex" behavior and the behavior for seeking "help", physical, psychologic and economic pressure, free and uncontrolled companion-relation, unavailability of condom in the room, and con-dom package which is not in accordance with the street commercial sex workers char-acteristic. This research results serve as a preliminary study of the need, which will be developed in to a comprehensive promotion strategy. Keywords: sexually transmitted diseases and HIV/AIDS, sexual behavior, negotiation, health promotion strategy and practice